Global Financial Stability Report, March 2003 : Market Developments and Issues. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2003)
This March 2003 issue of the Global Financial Stability Report highlights that the supportive stance of monetary policy in the major economies, coupled with more risk-averse behavior by both institutional and retail investors, has contributed to a sizable buildup of cash positions. A partial mobilization of these cash positions in the fourth quarter of 2002 helped fuel a short-lived stock market rally, led to a narrowing of credit spreads on mature and emerging bonds, and contributed to an increase in flows to emerging market borrowers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet